Screen for colorectal cancer in patients with idiopathic deep vein thrombosis. Issue 1 (2011) - Ribeiro, Andressa; Oliveira, André Luís Cozetto de; Silva, Adinaldo Menezes; Miquelin, Daniel; Reis, Luis Fernando
No abstract available